Analisis Teori Victim Precipitation terhadap Korban Hate Speech Pengguna Secreto Site di Aplikasi X - Raisha Hikmat; Muhammad Zaky (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Hate speech is the least reported crime by victims. This could indicate that society’s awareness of the importance of ethical behavior on social media is still low, and hate speech is considered as ordinary thing for them. The growth of anonymous messaging sites or apps on social media makes hate speech easier to commit. One of them is Secreto Site, which is relatively easy to use as others can access the link by simply sharing it. This study employs a qualitative approach aimed at exploring and digging deeper into the involvement of hate speech crime victims who use Secreto Site in on X. Mendelsohn proposed one of the victim typologies that aligns with the results of the research, which is the involvement of the victim in the crime.